Protección internacional para los desplazados ambientales: un análisis de la normativa actual y alternativas de mejora - Garcia Calderon, Maria Ines (2025)
The objective of this article is to present an analysis of the current international law regarding the protection received by displaced persons as a result of climate change and natural disasters. It also discusses some alternatives to improve the protection of this group. To this end, the text initially addresses the issue of forced displacement due to environmental causes. In light of the increasing number of displacements due to these causes, the topic of environmental migrants has gained much greater relevance. An analysis is made of the terminology used to refer to this type of migrant, the applicability of the 1951 Geneva Convention, as well as other actions and international instruments that have been adopted over the years. Throughout the article, the lack of a consensual international legal framework to protect these migrants is highlighted. Although efforts to overcome this, such as the Guiding Principles on Internal Displacement, the Nansen Initiative, and cooperation between governments and international organizations, are ongoing, their protection remains insufficient and inconsistent. The use of international human rights law and humanitarian law offers broader protection, especially in the context of the principle of non-refoulement.